Design, implementation, and analysis of next generation optical networks : b emerging research and opportunities - Imtiaz, Waqas Ahmed 1985; Roka, Rastislav 1972 (Advances in wireless technologies and telecommunication (AWTT) book series, 2020)
"This book provides insight about the requirements for high capacity next generation optical networks and address different technologies along with passive optical access networks. It also examines the basic requirements, techniques, and methods for designing, implementing, and analyzing a feasible next generation optical network"--